Studi Literatur Peran Akuntansi Manajemen dalam Pengambilan Keputusan Bisnis - Auril, Sheryn Alivia (Maliki Interdisciplinary Journal, 2025)
Effective decision-making in business requires more than intuition alone, but must also be based on the analysis of accurate data and information. Management accounting plays an important role in this process by providing financial data that supports planning, controlling, and evaluating performance. This article discusses how management accounting assists in strategic decision-making through cost analysis, budgeting, and profitability evaluation. This article reviews the literature on how the concept of decision making in business as well as how the role of accounting in business decision making. This research uses a descriptive-analytical approach with an emphasis on qualitative descriptive analysis and previous research. In addition, this article also discusses factors that affect the effectiveness of management accounting, such as top management support and technological readiness, are also outlined. Although there are advantages and limitations in management accounting, a good understanding of both can assist companies in making better decisions and achieving business goals more efficiently.